2023
DOI: 10.1007/s11104-023-05892-0
|View full text |Cite
|
Sign up to set email alerts
|

Carrot genotypes differentially alter soil bacterial communities and decomposition of plant residue in soil

Abstract: Purpose Farmers need alternative approaches to manage nitrogen (N) that meet crop needs while reducing loss to the environment. Identifying crop genotypes that promote decomposition of organic materials and understanding the potential mechanisms responsible could help address this challenge. Consequently, we aimed to 1) determine whether carrot genotypes differ in their potential to facilitate organic matter decomposition in soil, and 2) identify bacterial taxa that are stimulated by carrot roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…The results of this study suggest that plant-soil microbe interactions are influenced by trait breeding in organic carrot. This aligns with previous findings that carrot genotypes host distinct root-associated microbiomes that potentially differ in their functionality (Triviño et al 2023, Abdelrazek et al 2020). Moreover, we show that root exudation patterns were distinct across genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study suggest that plant-soil microbe interactions are influenced by trait breeding in organic carrot. This aligns with previous findings that carrot genotypes host distinct root-associated microbiomes that potentially differ in their functionality (Triviño et al 2023, Abdelrazek et al 2020). Moreover, we show that root exudation patterns were distinct across genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrsosphaeraceae was positively associated with genotypes NR and H; Nitrsosphaeraceae is an ammonia oxidizing bacteria, which are considered indicators of soil health (Mundepi et al 2019). These results align with observations that genotype NR hosts distinct N-associated functions (e.g., ammonia oxidation; Triviño et al 2023). Genotype H was additionally enriched with members of the Chitinophagaceae , a family identified as containing N fixing taxa, at midseason (Martin et al 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It indicated that both plant species and interspecific competition can change the abundance of dominant bacteria, which is due to their adaptability to a new microenvironment [57,58]. Moreover, the beneficial species (i.e., Bacillaceae, Xanthobacteraceae, Streptomycetaceae, Paenibacillaceae, Planococcaceae, Micromonosporaceae) can favor plant growth and improve nutrient availability by stimulating plants to secrete auxin while simultaneously fixing nitrogen, solubilizing phosphate, and decomposing organic matter [59][60][61][62][63][64]. Apart from their ability to stimulate plant growth, Bacillaceae, Streptomycetaceae, and Geodermatophilaceae can prevent plants from soil-borne disease and abiotic stresses (e.g., drought) through the synthesis of substances akin to lipopeptides that make plants more resistant to external stresses [65,66].…”
Section: Effect Of Interspecific Competition On Bacterial Community D...mentioning
confidence: 99%